Women’s conceptions about menopause and climateric - Cecília Nogueira Valença; Raimunda Medeiros Germano (Rev Rene)
It is a descriptive-exploratory study with qualitative and quantitative approach that aims to identify how much knowledge women have about climateric, their signals and symptoms and ways of accomplishing self-care. 50 women from 45 to 59 years-of age participated in a reproductive health center in Natal/RN who answered a semi-structured interview. A content analysis technique was used to collect the data. As a result, 84% of women had heard about what the climateric is; and 94% about menopause, but they were confused about climateric and menopause, getting older and illness. The climateric was revealed as anxiety, artralgias/mialgias and hot waves. Important ways to reach the quality of life were considered: physical activity, healthy intake and avoid smoking. It is essential that women have access to health information to understand changes of climateric/menopause, avoiding/easing the climateric syndrome and exercising self-care.